IMPROVING COMPOSITION ABILITY THROUGH SERIES IMAGE MEDIA IN BIPA LEARNING TO MALAY-INDONESIA STUDENTS OF HANKUK UNIVERSITY OF FOREIGN STUDIES SOUTH KOREA - Agus Sulaeman (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
This classroom action research aims to improve the ability to compose through serial image media in learning Indonesian for foreign speakers of Korean for the first time in an audiovisual course for 4th semester students. This research conducted on 30 semester 4 students, consisting of 15 male students and 15 female students. The learning used in this research is classroom action research with the Kemmis and McGartgart spiral model. Improved test scores compose of initial requirement of cycle I to cycle III is the average value at the beginning conditions was 59.67 with a completeness percentage of 43.33% (13 students), in cycle I it increased to 65.33 with a completeness percentage of 60% ( 18 students), in cycle II it increased to 72 with a completeness percentage of 73.33% (22 students) and in cycle III it increased to 75.66 with a completeness percentage of 86.66% (26 people). The results obtained from the class action research on 30 students, namely by increasing the average value of the initial conditions of 59.67 increased to 65.33 in cycle I, in cycle II increased to 72 and in cycle III increased to 75.66. It can be concluded that serial picture media in Indonesian language learning for foreign speakers of composing material can improve the writing ability of Malay-Indonesian study program students. Educators can use serial picture media as learning media which can improve students' composing abilities, so that students can easily develop ideas. or his mind in composing.